Microcellulose from Betel Husk Fiber as Filler in Bioplastic - Kuswariyah, Ratmi; Sitorus, Berlian; Adhitiyawarman, Adhitiyawarman; Antonius, Antonius (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2023)
Betel nut husk fiber has a reasonably high cellulose content. Meanwhile, bioplastics nowadays are mostly made of Poly Vinyl Alcohol (PVA), with one of its limitations being tensile strength and other properties regarding mechanical. Thus, this study aims to isolate microcellulose from areca nut fiber and use the fiber as a filler in bioplastic, where cellulose is combined with PVA. The intention is to understand the effect of adding microcellulose from betel nut fibers on the properties, including the biodegradability of PVA-based bioplastic films. This research has three steps: isolating cellulose from betel nut peel fibers by delignification, pulping, and bleaching. The next step is hydrolysis to obtain microcellulose. The last is the preparation of bioplastic films using the solution casting method, with five different ratios of microcellulose content in the bioplastic. The cellulose characterization from FTIR spectra shows the absorption of several peaks, such as O-H, C-H, and C-O functional groups. The mechanical testing results on the variation of bioplastic show that the bioplastic with the best characteristics was PL5, which has the highest microcellulose content, 8 MPa and 10.2% for tensile strength and elongation, respectively. The biodegradation test for bioplastic variation (PL5) was 82% within eight weeks, while in Indonesian National Standard (SNI) number 7188.7:2016, it is 100% within 60 days.